Generalized Spline Approach For Solving System of Linear Fractional Volterra Integro-Differential Equations - Hasan, Nabaa Najdi; Hussien, Doaa Ahmed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
In this paper generalized spline method is used for solving linear system of fractional integro-differential equation approximately. The suggested method reduces the system to system of  linear algebraic equations. Different orders of fractional derivative for test example is given in this paper to show the accuracy and applicability of the presented method.